Early Stage Rehabilitation for Strain Hamstring : A case report: Tahap awal Rehabilitasi pada kondisi strain hamstring - Anggiat, Lucky (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. This study's purpose is to report on the early stage physiotherapists' intervention on patients with hamstring strains as recommended in the early stage management of sports injuries. Materials and methods. This study is a case report from of a patient who has a hamstring strain with complaints of pain and decreased range of motion of the knee joint. Physiotherapists provide ultrasonic therapy with isometric contraction exercises on the hamstring muscles for 4 sessions for 2 weeks. Results. Ultrasound therapy and isometric contraction exercises increased the range of motion of the knee joint by 60% (active) and 50% (passive). Pain reduction also occurred by 83% for active motion pain and 80% for passive motion pain. Conclusions. The physiotherapy interventions with ultrasonic therapy and isometric contraction exercise therapy is in accordance with the early stage rehabilitation for the case of hamstring strains. With the interventions, the patient experienced a decrease in pain and an increase in Range of Motion from the knee joint.